Discourse on Legal Expression in Arrangements of Corruption Eradication in Indonesia - Hidayat, Shubhan Noor; Karjoko, Lego; Hermawan, Sapto (JILS (Journal of Indonesian Legal Studies), 2020)
The purpose of this research is to explain and examine the expansion of the absolute competence of the Administrative Court (hereinafter referred to as PTUN) after the Government Administration Law is promulgated and the implications of the application of the Administrative Law on legal certainty to eradicate and enforce corruption in Indonesia. This research uses a normative juridical research method and uses a statutory approach (statute approach). The results showed "that there are several forms of expansion of PTUN competencies, such as the authority that acts factually, the authority, administrative authorization, decide on positive fictitious decisions, and discretionary trials". Meanwhile, the implications of the Government Administration Law on corruption are known as corruption crimes, which are true. So, in this context, there are at least two problems, namely: Ã¢â‚¬Å“1. If the authorized court case is carried out by the state government which is submitted to the court simultaneously, to the State Administrative Court and to the District Court in a corruption case? 2. If at any time a PTUN decision has been issued stating that it is not authorized, but there is also a party who submits the case to the District Court on charges of corruption. What is the attitude of the District Court, whether to accept the PTUN decision on the case or choose to override the PTUN decisionÃ¢â‚¬Â. So the author is of the view that in this case there is concern that it will complicate the prosecution or eradication of criminal acts of corruption in the case of abuse of authority committed by government officials.